Ethanol extract of Centella asiatica improved methamphetamine-induced neurotoxicity on mouse model via stimulating superoxide dismutase II and microRNA-34A expression - Nursyamila Shamsuddin; Mazatulikhma Mat Zain; Mohd Ilham Adenan; Mohd Shihabuddin Ahmad Noorden (Penerbit Universiti Kebangsaan Malaysia, 2023)
Neurotoxicity induced by a psychostimulant drug, methamphetamine (METH) is associated with devastating and persistent neurotoxicity effects on the central nervous system (CNS). Centella asiatica (CA) is known as an antioxidant and neuroprotective agent. However, there is a limited study on natural-derived therapeutic to attenuate neurotoxicity induced by METH. We aimed to investigate the effects of METH and ethanol extract CA (CAE) on motor performance of animal model and the expression of manganese superoxide dismutase II (SOD2) and microRNA-34a (miR-34a) in the brain tissue. Male Sprague-Dawley rats were administered with METH (50 mg/kg per body weight) twice per day for 4 days, CAE (300 mg/kg & 500 mg/kg per body weight for 21 days and combination of METH and CAE for 21 day(s). Weight of rat was measured and motor performance was evaluated using vertical pole and narrow beam tests. Expression of SOD2 and miR-34a were measured using Quantitative Real-time Polymerase Chain Reaction (RT-qPCR). Group III (300 mg/kg CAE); p<0.001, Group IV (500 mg/kg CAE); p<0.001, Group V (METH+300 mg/kg CAE); p<0.01 and Group VI (METH+500 mg/kg CAE); p<0.01 significantly improved latency in the vertical pole test compared to METH group. Meanwhile, Group III (300 mg/kg CAE); p<0.001 and Group IV (500 mg/kg CAE); p<0.001 significantly decreased latency in the narrow beam test compared to METH. Post-treatment of CAE on METH-treated rats, Group V (METH+300 mg/kg CAE) and Group VI (METH+500 mg/kg CAE) nonsignificantly upregulated the SOD2 expression by 3.78±1.03 and 4.05±0.19 folds compared to METH, respectively. Post-treatment of CAE on METH-treated rats, Group V (METH+300 mg/kg CAE) and Group VI (METH+500 mg/kg CAE) non-significantly upregulated the miR-34a expression by (7.02±3.73) and (6.75±1.94) folds compared to METH, respectively. CAE could be suggested as a promising natural-derived therapeutic for METH-induced neurotoxicity to ameliorating motor performance and triggering SOD2 and miR-34a expression.